Lighting with organophosphorus materials: solution-processed blue/cyan light-emitting devices based on phosphaphenalenes - Hindenberg, Philip; Zimmermann, Johannes; Hernandez-Sosa, Gerardo; Romero-Nieto, Carlos (Dalton transactions, 2019)
A family of electroluminescent organophosphorus materials for solution-processed organic light-emitting diodes is reported. The investigated systems present a six-membered phosphorus heterocycle fused with a pyrrole or benzopyrrole moiety. The materials exhibit high thermal stability and are soluble in a variety of organic solvents. Already in very simple OLED architectures, the novel electroluminescent materials display blue or cyan luminescence; i.e. color coordinates x = 0.18; y = 0.21 and x = 0.22; y = 0.30, respectively, with performances that are in the range of state-of-the-art phosphazene materials. In electrofluorochromic devices, the color emission coordinates of the organophosphorus materials are tuned upon applying an electric potential. These findings set the bedrock for the development of new generations of organophosphorus light-emitting devices.
Gesehen am 16.12.2019